Review of Renal Artery Stenosis and Hypertension: Diagnosis, Management, and Recent Randomized Control Trials - Sadiq F Arab; Ahmed A Alhumaid; Mahmoud Tawfiq Abu Alnasr; Talal A Altuwaijri; Hesham Al-Ghofili; Mussaad M Al-Salman; Abdulmajeed Altoijry (Saudi Journal of Kidney Diseases and Transplantation, 2022)
Renal artery stenosis is one of the most common causes of secondary hypertension (HTN). Renal artery stenosis-induced HTN can occur in the presence of unilateral or bilateral narrowing and a solitary kidney with stenotic artery, which may subsequently lead to renal insufficiency (e.g., ischemic kidney disease) or pulmonary edema. Renal artery stenosis can be diagnosed using multiple modalities, including Doppler ultrasound, computed tomography angiography, magnetic resonance angiography, or selective angiogram. Although atherosclerotic renal artery stenosis management in patients with HTN has been greatly controversial, it is inevitable in the treatment of some selected cases. These cases can be treated by either percutaneous angioplasty (with or without stenting) or less common, open surgical approach revascularization, both of which have excellent primary patency rates. Generally, several trials on renal artery angioplasty or stenting in patients with atherosclerotic disease have shown that the long-term benefits in terms of blood pressure control and renal function over pharmacological management is not substantial. Furthermore, studies could not demonstrate a prolongation of event-free survival after renal vascularization. Moreover, endovascular procedures have substantial risks. Careful patient selection is required when considering revascularization, for including those with refractory HTN or progressive renal failure, to maximize the potential benefits. This paper discusses the epidemiology of atherosclerotic renal artery stenosis and its clinical presentation, diagnosis, treatment, prognosis, and future perspectives.